2022
DOI: 10.1016/j.respol.2020.104143
|View full text |Cite
|
Sign up to set email alerts
|

Implied comparative advantage

Abstract: The comparative advantage of a location shapes its industrial structure. Current theoretical models based on this principle do not take a stance on how comparative advantages in different industries or locations are related with each other, or what such patterns of relatedness might imply about the underlying evolution of comparative advantage. We build a simple Ricardian-inspired model and show that hidden information on inter-industry and inter-location relatedness can be captured by simple correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…Comparative advantage is the ability of an economy to produce a particular good or service at a lower opportunity cost than its trading partners [19]. Comparative advantage is used to explain why a firm, country, or individual can profit from trade [20]. When used to describe international trade, comparative advantage refers to products that a country can produce more cheaply or more easily than other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparative advantage is the ability of an economy to produce a particular good or service at a lower opportunity cost than its trading partners [19]. Comparative advantage is used to explain why a firm, country, or individual can profit from trade [20]. When used to describe international trade, comparative advantage refers to products that a country can produce more cheaply or more easily than other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study indicated that the impact of the influencing factors on the environmental tax revenue in different regions was heterogeneous, which was highly related to the degree of economic development in each region. Therefore, one efficient way towards protecting the environment and promoting economic development by environmental tax revenue is to constantly develop the economy by local conditions, such as resource endowment and development orientation according to comparative advantage theory [ 27 ]. In addition, the decision-makers should also consider reducing the tax burden of other taxes, such as value-added tax and enterprise income tax, so that the overall tax burden can be reduced or unchanged and the cost can be reduced.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 99%
“…See, for example, ArnaudCostinot & Dave Donaldson (2012);Weder (2017); Douglas A Irwin (2017)Krugman, Obstfeld & Melitz (2018);Eduardo Crespo, Ariel Dvoskin & Guido Ianni (2021); andRicardo Hausmann, Daniel P. Stock & Muhammed Yildirim, (2021).…”
mentioning
confidence: 99%